Laproscopic cholecystectomy an analysis of 787 cases with reference to predictors on level of difficulty and the influence of early conversion to reduce IBDI and other complications - Kalyanasundar, Suresh; Bhatnagar, Ashok (International Surgery Journal, 2017)
Background: Laparoscopic cholecystectomy is the most common major elective surgical procedure all over the globe. The complications associated with the procedure also become important for surgeons to manage well, strive to prevent them from occurring. Methods: The study was prospective and involved 787 cases in a period of 60 months starting from January 2013 to January 2017 which were diagnosed to have cholelithiasis sonologically, features to suggest acute cholecystitis and a normal CBD, with normal liver function tests, clinical examination did not reveal a palpable lump in the right hypochondrium and the history of acute pain was less than 72 hours. Results: The total number of cases 787 and 127 (16%) there were complications of which 0.2 % was biliary injuries and rest were nonbiliary. IBDI occurred in 02cases in this series which is 0.25% and 125 cases there was Nonbiliary complications. The incidence of iatrogenic bile duct injury (IBDI) in LC is 0.4%- 1.3 % compared to 0.2%- 0.3% for OC. 108 cases were converted to an open procedure (13%) and the average rate globally 5 % to 10%. Conclusions: LC should be planned in all cases of cholelithiasis, it is helpful to preoperatively and operatively grade the cases for the operative ease and cases which fall in the category of extreme it is better to resort to conversion early or even a planned open surgery. The low complication rate especially biliary is because of a careful planning preoperatively and operatively as per prediction scales which we used, a low tolerance to conversion and because of adopting the practice of subtotal cholecystectomy.